2020
DOI: 10.1186/s12929-020-00642-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term expansion of directly reprogrammed keratinocyte-like cells and in vitro reconstitution of human skin

Abstract: Background: Human keratinocytes and derived products are crucial for skin repair and regeneration. Despite substantial advances in engineered skin equivalents, their poor availability and immunorejection remain major challenges in skin grafting. Methods: Induced keratinocyte-like cells (iKCs) were directly reprogrammed from human urine cells by retroviral transduction of two lineage-specific transcription factors BMI1 and △NP63α (BN). Expression of keratinocyte stem cell or their differentiation markers were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 88 publications
1
4
0
Order By: Relevance
“…The UGCG, keratin (KRT), late cornified envelope (LCE), and small proline-rich protein (SPRR) families are essential factors for keratinocyte differentiation (Figure 4c,d). Differentiated keratinocytes replenish the upper layer and desquamate the dead cells to renew the skin [62]. These results suggest that the olive-derived phenolic compounds might inhibit melanoma growth by disrupting pathways and the cell cycle in melanoma, and might provide the underlying molecular mechanism of the anti-cancer effects of OL and OC reported in previous studies [63][64][65][66].…”
Section: Hierarchical Clustering Of Degs Of Enriched Functions In Ol-...supporting
confidence: 53%
“…The UGCG, keratin (KRT), late cornified envelope (LCE), and small proline-rich protein (SPRR) families are essential factors for keratinocyte differentiation (Figure 4c,d). Differentiated keratinocytes replenish the upper layer and desquamate the dead cells to renew the skin [62]. These results suggest that the olive-derived phenolic compounds might inhibit melanoma growth by disrupting pathways and the cell cycle in melanoma, and might provide the underlying molecular mechanism of the anti-cancer effects of OL and OC reported in previous studies [63][64][65][66].…”
Section: Hierarchical Clustering Of Degs Of Enriched Functions In Ol-...supporting
confidence: 53%
“… 23 This could be explained based on the expression of the calcium-sensing receptor (CaSR); keratinocytes that express CaSR respond to calcium stimulation during differentiation. 26 Subsequently, Zheng et al 24 showed that the combination of Bmi1 and DNp63α (BD cocktail) can also generate iKSCs from human urine cells that can be cultured for a long-term and can self-assemble to form stratified skin equivalents in vitro under high extracellular calcium conditions. However, the BD cocktail-mediated reprogramming of fibroblasts is less efficient compared to that of human urine cells, and these fibroblast-derived iKSCs cannot form colonies, suggesting that different induction protocols target specific cell types and differentiation might be influenced by the genetic background.…”
Section: Direct Lineage Reprogramming To Generate Ikscsmentioning
confidence: 99%
“…However, the BD cocktail-mediated reprogramming of fibroblasts is less efficient compared to that of human urine cells, and these fibroblast-derived iKSCs cannot form colonies, suggesting that different induction protocols target specific cell types and differentiation might be influenced by the genetic background. 24 Kurita et al showed for the first time the application of in situ reprogramming in skin repair of animal model. 25 In mice, transduction using adeno-associated viruses (AAV) carrying DNp63α, grainyhead-like 2 (GRHL2), transcription factor AP-2 alpha (TFAP2a), and c-Myc (DGTM cocktail) can induce the conversion of the mesenchymal cells into skin-like epithelial cells at the site of injury, and these cells could proliferate and accelerate wound healing.…”
Section: Direct Lineage Reprogramming To Generate Ikscsmentioning
confidence: 99%
See 1 more Smart Citation
“…To induce reprogramming of human urine cells into iNPCs, human UCs were infected in various combinations of the retroviruses expressing SIX1, SIX2, OSR1, PAX2, OCT4, SOX2, KLF4, c-MYC, and SLUG. As previously established [57,58], these retroviruses were produced by the human 293-derived retroviral packing cell line transfected with pMXs-based retroviral vectors encoding hOCT3/4 (Plasmid #17217), hSOX2 (Plasmid #17218), hKLF4 (Plasmid #17219), hc-MYC (plasmid #17220) and SLUG using Lipofectamine 2000 (Life Technologies, Waltham, MA, USA), according to the manufacturer's instructions. At 96 h post-transfection, retrovirus containing supernatants were harvested, filtered with a 0.45 µm sterile syringe filter (Millipore, Burlington, VT, USA), and concentrated at 20,000× g for 2 h at 4 • C. Human-derived UCs were seeded in a gelatin-coated 6-well plate and, 24 h later, exposed to the concentrated retrovirus in the presence of 4 µg/mL polybrene (Sigma, St. Louis, MO, USA).…”
Section: Generation Of Inpcsmentioning
confidence: 99%